Protein RepC is involved in copy number control of the broad host range plasmid RSF1010. - Haring, V (1985)
Essential replication (rep) genes of the broad host range plasmid RSF1010 have been cloned onto controlled expression vectors and their protein products have been visualized, after induction, by NaDodSO4/polyacrylamide gel electrophoresis of whole cell lysates. During this induction the replication of a coresident RSF1010 replicon, pKT210, was analyzed by quantitative DNA X DNA hybridization. The initiation of pKT210 replication was stimulated 6-fold by a simultaneous overproduction of the RepA and RepC proteins compared to cells in which only the RepA protein was overproduced. An enhanced synthesis of the RepB protein resulted in a 1.6-fold stimulation of pKT210 replication, whereas an overproduction of the RepA protein alone had no effect. Purified RepC protein has been shown to bind preferentially to DNA carrying the replication origin of RSF1010. Within this segment it was bound specifically to those DNA fragments that contained the 20-base-pair direct repeats of the origin region. These results suggest that RepC protein acts as a positive replication regulator, that its concentration is rate-limiting, and that the replication rate of RSF1010 is controlled, at least in part, at the level of RepC synthesis.